IMPLEMENTASI MODUL AJAR PENDIDIKAN AGAMA ISLAM DAN IMPLIKASINYA TERHADAP KEAKTIFAN BELAJAR MURID KELAS VIII SMP NEGERI 4 PEKALONGAN - Dewi, Irsilawati; Anisatul Haniah; Yurid Ilyuna; Sevi Selviani Putri; Risqi Andini; Moh.Nasrudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of Islamic Religious Education (PAI) teaching modules and their implications for students' learning activeness in Grade VIII of SMP Negeri 4 Pekalongan. This research employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving Islamic Religious Education teachers and students. The findings indicate that the implementation of teaching modules was carried out flexibly by combining various learning resources and interactive learning methods such as question-and-answer sessions and small group discussions. The teaching modules helped teachers organize learning activities systematically while providing opportunities for students to participate actively in the learning process. Students’ learning activeness was reflected in their involvement in discussions, answering questions, expressing opinions, taking notes, and completing learning tasks. Supporting factors included varied teaching methods, contextual learning materials, and a conducive classroom environment. Meanwhile, the obstacles encountered were limited instructional time, differences in students' readiness and abilities, and students' lack of confidence. Teachers addressed these challenges through personal approaches, peer tutoring, and engaging learning activities. The study concludes that the implementation of PAI teaching modules contributes positively to enhancing students' learning activeness and supports student-centered learning practices.